Building Information Modeling (BIM) Application in Construction Waste Quantification—A Review - Usman Aftab; Farrokh Jaleel; Mughees Aslam; Muhammad Haroon; Rafiq Mansoor (Engineering Proceedings)
The construction industry is known for poor performance, low productivity, high waste generation, and for lagging in the adoption of new technology. A high rate of material wastage in construction projects has economic and environmental implications for concerned stakeholders. Construction waste quantification is an essential requirement for formulating waste management strategies. Technological advancements like building information modeling (BIM) and artificial intelligence (AI) provide effective solutions to the construction industry to deal with these prevalent issues. This literature review-based study observes the scarcity of research on the application of BIM in construction waste quantification. The limited number of studies found in the literature confirm the ability of BIM-aided waste quantification models to forecast waste generation. Moreover, the application of these models can also assist in reducing waste to a considerable extent. This study recommends that further studies should be conducted on technology-assisted waste quantification in building and infrastructure projects to evaluate their effectiveness for subsequent implementation in the industry.